Exploring Student Motivation: Teaching Students Specializing in EU English - Koltai, Andrea (Working Papers in Language Pedagogy, 2012)
The present paper reports on a qualitative study involving a group of Hungarian university students learning the specialized language of the EU in English. The purpose of the study is to explore students’ motivation to learn EU English and to see whether the results of the interviews analyzed could lead to an improvement of the course syllabus and the teaching materials. Data were collected through semi-structured interviews conducted with university students, as well as through two interviews with teachers, focusing on their students’ motivational characteristics, and from the author’s own teaching diary. Results show that identifying student motivation to learn EU English is a crucial step in designing syllabi or teaching materials for EU English courses, as it facilitates the definition of the actual course objectives and supplies teachers with useful information on their students’ beliefs, wishes, and immediate and future goals. The results of the study are assumed to be of assistance to teachers of EU English courses in considering specific student needs when selecting relevant course content and compiling teaching materials.